Niche overlap and resource partitioning among five sympatric bufonids (Anura, Bufonidae) from northeastern Argentina - Duré Pitteri, Marta Inés (2009)
The niche overlap and resource partitioning were analyzed for five sympatric bufonids from Northeastern Argentina: Rhinella schneideri, R. bergi, R. fernandezae, R. granulosa, and Melanophryniscus cupreuscapularis. The primary objectives were to analyze the diet and pattern of coexistence relative to the microhabitats among species. The bufonids, which are primarily terrestrial, exhibited a preference for small, hard prey such as formicids or coleopterans. The smallest species preferably consumed ants, while R. schneideri preferred beetles. Significant differences were detected for the diets of these five species. In addition, significant overlap in the trophic niche was noted for all species except between R. granulosa and R. schneideri. Studying the diet behaviors and trophic parameters of sympatric species provides important data for understanding the community and for the development of conservation guidelines.